Lead, Cadmium and Nickel Accumulation in Some Common Spices Grown in Industrial Areas of Bangladesh (The Agriculturists, 2014)
Chemical analysis was conducted to determine the contents of lead (Pb), cadmium (Cd) and nickel (Ni) of three common spices viz, onion (Allium cepa), garlic (A. sativum) and chilli (Capsicum annuum) and their rhizospheric soils grown in polluted and non-polluted areas of Gazipur city in Bangladesh. Plant and rhizospheric soil samples were collected from: (i) directly polluted (Kaliakoir, Konabari, Gazipur), (ii) indirectly polluted (Donker bill, East Kaliakoir, Konabari, Gazipur), and iii) non-polluted (Bangladesh Agricultural Research Institute, Joydebpur, Gazipur) areas. Regardless of the locations, there were significant differences (P?0.01) in Pb, Cd, and Ni concentrations in all spices and soils. The concentrations of Pb, Cd and Ni were in the order of Ni>Pb>Cd in the spices and degrees of pollution in soils were in the order of directly polluted>indirectly polluted>non-polluted area. The Pb, Cd and Ni contents were found higher in garlic followed by chilli and onion in three areas. Most of the metals were accumulated in bulb/fruit, moderate in root and the smallest in the leaf. Compared to the non-polluted area, the higher amount of Pb, Cd and Ni were detected in both soils and spices samples collected around industrial areas of Gazipur city. Alarmingly, all the spices contained Pb, Cd, and Ni were higher than the tolerance limits proposed by Food and Agricultural Organization (FAO)/World Health Organization (WHO) and State Environmental Protection Administration (SEPA). Therefore, it is strongly recommended not to grow spice crops in polluted areas. DOI: http://dx.doi.org/10.3329/agric.v12i1.19867The Agriculturists 2014; 12(1) 122-130